THE EFFECT OF LIFE INSURANCE CLAIM FILING SYSTEM DEVELOPMENT ON INCREASING CUSTOMER SERVICE PERFORMANCE (CASE STUDY: PT. ASURANSI ALLIANZ LIFE INDONESIA KPM. MAKASSAR) - Markani Pato; Lilis Sugianti; Askar Askar; Febri Hidayat Saputra; Asrul Asrul; Mashud Mashud; Asnimar Asnimar; Muhammad Resha; Neneng Awaliah (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Customer comfort is absolute and needs to be fully attentive to improving service performance, especially companies in the service sector. Submission of life insurance claim pt. Allianz Life Indonesia Insurance still uses conventional methods where when the customer wants to submit an insurance claim, the customer must visit the branch office, website or contact the head office to get information on what requirements are needed to submit a claim. This problem requires a flexible system application that helps customers in submitting claims and companies in processing customer data. This study aims to create a claim submission information system for PT. Allianz Life Indonesia Insurance KPM. Makassar to make it easier for customers to reach claim submissions without having to visit a branch office. Data obtained by: 1. Field research, 2. Interview with PT. Allianz Life Insurance Indonesia. System development using RAD (Rapid Application Development) model. System development using the RAD (Rapid Application Development) model. This model has 3 stages, namely 1. Requirement Planning, 2. Design 3. Implementation. The results showed that the results of testing with the UAT (User Acceptance Testing) technique were obtained by 82,75% of 26 respondents including admins, pimipinan and customers. The test results, it shows that the information system for submitting life insurance claims is declared feasible and can improve customer service performance